Immune cells inhibit the tumor metastasis in the 4D cellular lung model by reducing the number of live circulating tumor cells. Issue 1 (December 2018) - Mishra, Dhruva; Rocha, Humberto; Miller, Ross; Kim, Min
Abstract The immune system and tumor microenvironment play a decisive role in tumor progression. We developed a novel model to better understand tumor progression and interaction with immune cells and the cellular components. We grew 393 P non-metastatic and 344SQ metastatic murine cells in an acellular metastatic lung cancer model, where both cell lines formed circulating tumor cells (CTC) and metastatic lesions. When the CTC from this model were placed in the tail vein of nu/nu mice, both cell lines formed metastatic lesions. However, in syngeneic immune-competent mice, the CTC from the non-metastatic cell line did not metastasize while the CTC from the metastatic cell line metastasized. When we placed the activated immune cells in the cellular lung model, it decreased CTC and metastatic lesion formation for the non-metastatic cell line while it had no impact on metastatic cell line. The metastatic cell line had a significant increase in expression of programmed death-ligand 1 (PDL-1) compared to the non-metastatic cell line in the model. Overall, the immune cells showed an impact on viability of CTC for cell lines with a decreased expression of PDL-1 that leads to decreased metastatic lesion formation. Further studies are needed to understand the subtype of immune cells and mechanism of decreased CTC viability and metastasis inhibition.